Absorption, metabolism and excretion of darexaban (YM150), a new direct factor Xa inhibitor in humans. (June 2013) - Hashimoto, Tadashi; Suzuki, Katsuhiro; Kihara, Yukie; Iwatsubo, Takafumi; Miyashita, Aiji; Heeringa, Marten; Onkels, Hartmut; Groenendaal, Dorien; Verheggen, Frank; van Marle, Sjoerd; Usui, Takashi
<x xml:space="preserve">Abstract</x> 1. The absorption, metabolism and excretion of darexaban (YM150), a novel oral direct factor Xa inhibitor, were investigated after a single oral administration of [14C]darexaban maleate at a dose of 60 mg in healthy male human subjects. 2. [14C]Darexaban was rapidly absorbed, with both blood and plasma concentrations peaking at approximately 0.75 h post-dose. Plasma concentrations of darexaban glucuronide (M1), the pharmacological activity of which is equipotent to darexaban in vitro, also peaked at approximately 0.75 h. 3. Similar amounts of dosed radioactivity were excreted via faeces (51.9%) and urine (46.4%) by 168 h post-dose, suggesting that at least approximately half of the administered dose is absorbed from the gastrointestinal tract. 4. M1 was the major drug-related component in plasma and urine, accounting for up to 95.8% of radioactivity in plasma. The N-oxides of M1, a mixture of two diastereomers designated as M2 and M3, were also present in plasma and urine, accounting for up to 13.2% of radioactivity in plasma. In faeces, darexaban was the major drug-related component, and N-demethyl darexaban (M5) was detected as a minor metabolite. 5. These findings suggested that, following oral administration of darexaban in humans, M1 is quickly formed during first-pass metabolism via UDP-glucuronosyltransferases, exerting its pharmacological activity in blood before being excreted into urine and faeces.